The Sanskrit, Syriac and Persian sources in the Comprehensive book of Rhazes - Kahl, Oliver. (Islamic Philosophy, Theology and Science. Texts and Studies, 2015)
This work offers a critical analysis of the Sanskrit, Syriac and Persian sources in Rhazes' (d. 925 CE) Comprehensive Book (or al-Kitāb al-Ḥāwī), a hugely famous and highly unusual medico-pharmaceutical encyclopedia originally written in Arabic. All text material appears in full Arabic with English translations throughout, whilst the traceable Indian fragments are represented here, for the first time, in both the original Sanskrit and corresponding English translations. The philological core of the book is framed by a detailed introductory study on the transmission of Indian, Syrian and Iranian medicine and pharmacy to the Arabs, and by extensive bilingual glossaries of relevant Arabic and Sanskrit terms as well as Latin botanical identifications. The World Award for the Book of the Year of the Islamic Republic of Iran has selected this title as one the best books of the year 2015 in the field of Islamic/ Iranian Studies.